Effect of vanadium compounds on acid phosphatase activity - Vescina, Cecilia M. (1996)
The direct effect of different vanadium compounds on acid phosphatase (ACP) activity was investigated. Vanadate and vanadyl but not pervanadate inhibited the wheat germ ACP activity. These vanadium derivatives did not alter the fibroblast Swiss 3T3 soluble fraction ACP activity. Using inhibitors of tyrosine phosphatases (PTPases), the wheat germ ACP was partially characterized as a PTPase. This study suggests that the inhibitory ability of different vanadium derivatives to modulate ACP activity seems to depend on the geometry around the vanadium atom more than on the oxidation state. Our results indicate a correlation between the PTPase activity and the sensitivity to vanadate and vanadyl cation.